2006
DOI: 10.1002/ejoc.200600092
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis of Achiral and Chiral Cyclic Dehydro‐α‐Amino Acid Derivatives Through Nucleophilic Addition of Amines to β,γ‐Unsaturatedα‐Keto Esters

Abstract: A very simple and efficient synthesis of 3‐amino‐1,5‐dihydro‐2H‐pyrrol‐2‐ones is reported. These cyclic dehydro‐amino acid derivatives with a stereogenic center at the 5‐position were obtained by the addition of two equivalents of amine to β,γ‐unsaturated keto esters. These cyclic enamines can also be obtained by the three‐component reaction of ethyl pyruvate, amines and aldehydes. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2006)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 64 publications
(13 reference statements)
1
42
0
Order By: Relevance
“…Encouraged by these results, substituted dihydro-2-oxopyrroles with different [12][13][14][15][16][17][18][19][20][21][22]. Aliphatic amines include benzyl amine, n-butyl amine and cyclo hexyl amine were used and the corresponding products were achieved in good to high yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraged by these results, substituted dihydro-2-oxopyrroles with different [12][13][14][15][16][17][18][19][20][21][22]. Aliphatic amines include benzyl amine, n-butyl amine and cyclo hexyl amine were used and the corresponding products were achieved in good to high yields.…”
Section: Resultsmentioning
confidence: 99%
“…1. As a result, considerable efforts have been made for the synthesis of this important class of compounds [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the second step the reaction mixture was heated at 100 . ℃ To find optimized amount of SiO 2 -FeCl 3 , the reaction was carried out by varying amount of the catalyst and ethyl pyrovate ( [2][3][4]6 Using these optimized reaction conditions, the scope and efficiency of these procedures were explored for the synthesis of a wide variety of substituted 1,5-diaryl-3-(arylamino)-1H-pyrrol-2(5H)-ones (Scheme 1, Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…Previous routes to 1,5-diaryl-3-(arylamino)-1H-pyrrol-2(5H)-ones involve two-component condensation of amines with pyrrolidine-2,3-diones 2 and β,γ-unsaturated α-oxo esters. 3 Palacios and co-workers 4 reported that a one-pot three-component coupling of aniline, aldehyde and pyruvate in the presence of H 2 SO 4 would be the ideal process for the synthesis of these targeted molecules. Despite to this fact that homogeneous liquid acid catalysts suffer from several disadvantages such as high toxicity and also difficulty in separation and recovery, thus replacement of these conventional acids by solid heterogeneous catalyst is desirable to achieve effective and catalyst handling, product purification and decrease of waste production.…”
Section: Introductionmentioning
confidence: 99%
“…These heterocycles are also important reagents as materials for the synthesis of organic complexes [14]. In view of the importance of dihydropyrrol-2-one derivatives, several methods have been developed to synthesize these useful heterocycles [15][16][17][18][19][20]. Recently, the literature has presented some methods to synthesise polysubstituted dihydropyrrol-2-ones via MCRs using catalysts such as acetic acid (AcOH), iodine (I 2 ) , benzoic acid, titanium dioxide (TiO 2 ) nanopowder, Cu(OAc) 2 ÁH 2 O and (S)-camphorsulfonic acid [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%